2013
DOI: 10.1016/j.celrep.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Regulation of the H3K4 Methyltransferase Activity of PRDM9

Abstract: PRDM9, a histone lysine methyltransferase, is a key determinant of the localization of meiotic recombination hot spots in humans and mice and the only vertebrate protein known to be involved in hybrid sterility. Here, we report the crystal structure of the PRDM9 methyltransferase domain in complex with a histone H3 peptide dimethylated on lysine 4 (H3K4me2) and S-adenosylhomocysteine (AdoHcy), which provides insights into the methyltransferase activity of PRDM proteins. We show that the genuine substrate of PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 31 publications
6
123
0
Order By: Relevance
“…H3K36me3 is specifically enriched at recombination sites in a Spo11-independent manner PRDM9 catalyzes H3K36me3 formation in vitro (Wu et al 2013;Eram et al 2014), and H3K36me3 enrichment is detected in vivo at the center of mouse hotspots (Davies et al 2016;Powers et al 2016). Interestingly, we only detected this PRDM9-dependent H3K36me3 enrichment in class 1 PRDM9 binding sites and not in classes 2A or 2B (Fig.…”
Section: Prdm9 Binding Sites Without Recombination Activitymentioning
confidence: 60%
See 1 more Smart Citation
“…H3K36me3 is specifically enriched at recombination sites in a Spo11-independent manner PRDM9 catalyzes H3K36me3 formation in vitro (Wu et al 2013;Eram et al 2014), and H3K36me3 enrichment is detected in vivo at the center of mouse hotspots (Davies et al 2016;Powers et al 2016). Interestingly, we only detected this PRDM9-dependent H3K36me3 enrichment in class 1 PRDM9 binding sites and not in classes 2A or 2B (Fig.…”
Section: Prdm9 Binding Sites Without Recombination Activitymentioning
confidence: 60%
“…Different from S. cerevisiae, these hotspots are not preferentially located in promoter regions, but they are enriched in H3K4me3 (Buard et al 2009;Smagulova et al 2011), presumably through PRDM9 methyltransferase activity (Hayashi et al 2005). Indeed, PRDM9 can methylate histone H3 at K4, K9, and K36 in vitro (Wu et al 2013;Eram et al 2014;Koh-Stenta et al 2014). Like H3K4me3, H3K36me3 also can be associated with nucleosomes adjacent to hotspots (Buard et al 2009;Davies et al 2016;Powers et al 2016).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 96%
“…There have been reports of histone methylation activity by several PRDM proteins in addition to PRDM9 (Derunes et al 2005; Eom et al 2009; Pinheiro et al 2012); however, structural studies have suggested that these PR/SET domains lack residues necessary for binding to S -adenosyl methionine (Wu et al 2013), the cofactor that donates methyl groups for KMT activity. Extensive research by several groups, including our own, has failed to establish enzymatic activity for these enzymes.…”
Section: Molecular Mechanisms Of Set Domain Nonhistone Methylation Inmentioning
confidence: 99%
“…PRDM9 comprises an N-terminal Krüppel-associated box (KRAB) domain; a central PR-SET domain, known for catalyzing histone H3 Lys4 (H3K4) trimethylation (Hayashi et al 2005;Wu et al 2013;Eram et al 2014;Koh-Stenta et al 2014); and a C-terminal tandem array of multiple Cys2-His2 (C2H2) zinc fingers (ZnFs) (Fig. 1A;Supplemental Fig.…”
mentioning
confidence: 99%